Microplastics as an emerging threat to the freshwater ecosystems of Veeranam lake in south India: A multidimensional approach. (February 2021) - Bharath K, Manikanda; S, Srinivasalu; Natesan, Usha; Ayyamperumal, Ramamoorthy; Kalam S, Nirmal; S, Anbalagan; K, Sujatha; C, Alagarasan
Abstract: In the current scenario, microplastic, as a contaminant, is becoming an ecological threat to the freshwater ecosystem. The present study attempted to determine the quality and quantity of microplastic contaminants in water and soil samples at Veeranam lake in Tamil Nadu, India. It is very important to mention that the Veeranam lake in Tamil Nadu, is a major urban water source of the capital district of Tamil Nadu. Using Van Veen grab-sampling equipment and trawl methods, the study detected the presence of microplastics in 28 sediment samples and 31 water samples from the collected samples. In addition to this, the density separation was performed with zinc chloride solution using the Sediment-Microplastic Isolation (SMI) unit. The quantum of total plastic particle present in surface water were in the range of 13–54 items/km2 with a mean value of 28 items/km2. In the case of sediment samples, the amount of total plastic particle was found in the range of 92–604 items/kg with a mean value of 309 items/kg. The abundance of microplastic particles in water and sediments in various shape, colour, and composition as in the order of nylons > polythene > fibres/PVC > fragments > foam > pellets; dominant colours as white > red > black > green > blue and yellow at the sampling sites. In term of percentage of contaminant distribution, the study found that the collected water and sediment samples deposited with polymer type of plastic particles were nylon (39%), polyethylene (23%), polystyrene (19%), polypropylene (15%), and polyvinyl chloride (4%). The research work is a baseline study for the proposed site of Veeranam lake for microplastics contamination. Graphical abstract: Image 1 Highlights: Microplastics have been identified and distributed in the freshwater ecosystems. An abundance of microplastic particles in floating debris and lake bottom sediments averages 28 (items per square km 2 ) and 309 items/kg. Microplastics vary in the order of nylons > polythene > fibers/PVC > fragments > foam > pellets.